2011
DOI: 10.2141/jpsa.010103
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of the Cuticle Layer of Avian Eggshells

Abstract: The structure and mineral composition of eggshell cuticles were studied in species of birds. The approximate thickness of the cuticle layer at the top of shell columns was about m in the Red Junglefowl ( ), about m in the White Pelican ( ), about m in the Japanese quail ( ), about m in the Greater Flamingo ( ) and about m in the Humboldt Penguin ( ). The matrix of the cuticle layer decalcified with EDTA was composed of vesicles in a variety of sizes in all birds. Major elements in cuticle materials detected by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 11 publications
1
34
0
1
Order By: Relevance
“…A higher cuticle coverage (P ≤ 0.001) was in eggs produced by Lohmann Brown compared to Isa Brown and Hy-Line Silver Brown. However, housing system did not significantly affect the cuticle coverage in Kusuda et al (2011) who concluded that the diversity in the structure of the cuticle layer may be linked to the environment of the nest, mainly humidity, which is hard to control in outdoor systems. Further investigation on the effect of genotype and housing management on cuticle deposition is needed because so-far available data are limited.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A higher cuticle coverage (P ≤ 0.001) was in eggs produced by Lohmann Brown compared to Isa Brown and Hy-Line Silver Brown. However, housing system did not significantly affect the cuticle coverage in Kusuda et al (2011) who concluded that the diversity in the structure of the cuticle layer may be linked to the environment of the nest, mainly humidity, which is hard to control in outdoor systems. Further investigation on the effect of genotype and housing management on cuticle deposition is needed because so-far available data are limited.…”
Section: Resultsmentioning
confidence: 99%
“…Eggshell cuticle is a very thin organic layer covering the eggshell surface and plugs the shell pores openings to limit water, gases, and bacterial penetration through the eggshell (De Reu et al 2006). It is composed of inner doi: 10.17221/75/2017-CJAS calcified and outer non-calcified water insoluble layers which are deposited directly onto the vertical crystal layer of the eggshell (Kusuda et al 2011). The structure of the eggshell is often expressed by eggshell quality characteristics including eggshell strength and thickness.…”
mentioning
confidence: 99%
“…It is composed of inner calcified and outer non-calcified water insoluble layers which are deposited directly onto the vertical crystal layer of the eggshell (Rose and Hincke 2009;Kusuda et al 2011). Unfor-doi: 10.17221/46/2015-CJAS tunately not all avian eggs have a cuticle layer, and the distribution of cuticle is often patchy (Bain et al 2009;.…”
Section: Eggshell Structure and Formationmentioning
confidence: 99%
“…Normally, the cuticle is likely to be under strong natural selection in birds such as pelicans or flamingos that live in damp and presumably more microbiologically challenging environments and that have much thicker cuticles than do chickens or quail (Kusuda et al . ). In modern egg production, to a large extent, the use of artificial incubation will have lessened the selection pressure for this trait.…”
Section: Introductionmentioning
confidence: 97%